2006
DOI: 10.1155/2006/536519
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry of the Side Population: Tips & Tricks

Abstract: Background: The Side Population (SP) has become an important hallmark for the definition of the stem cell compartment, especially in the detection of these cells and in their physical isolation by fluorescence-activated cell sorting (FACS). SP cells are CD34neg and were discovered using ultraviolet excitation based on the efflux of Hoechst 33342 (Ho342). Although the method works as originally described, we believe that this method is difficult for most investigators. First, because the ability to discriminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Malignant MOSE (M-L) cells were separated by FACS into two populations. SP cells actively pump the Hoechst 33342 dye out of the cells, while NSP cannot and therefore this is a way to isolate these two cell populations (22)(23)(24)(25)(26). The percentage of SP cells in M-L cells reached up to 24.4% (Fig.…”
Section: Identification Of Ovarian Cancer Stem Cells-like Cellsmentioning
confidence: 98%
See 2 more Smart Citations
“…Malignant MOSE (M-L) cells were separated by FACS into two populations. SP cells actively pump the Hoechst 33342 dye out of the cells, while NSP cannot and therefore this is a way to isolate these two cell populations (22)(23)(24)(25)(26). The percentage of SP cells in M-L cells reached up to 24.4% (Fig.…”
Section: Identification Of Ovarian Cancer Stem Cells-like Cellsmentioning
confidence: 98%
“…Our previous study demonstrated that the acquisition of stemness was closely associated with malignant transformation of MOSE cells (unpublished data). SP cells are an important hallmark for the definition of the stem cell-like characteristics (22)(23)(24)(25)(26); therefore, whether SP cells may be used to enrich ovarian CSCs was investigated. Malignant MOSE (M-L) cells were separated by FACS into two populations.…”
Section: Identification Of Ovarian Cancer Stem Cells-like Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…N. Shoutko, O. A. Gerasimova Open Journal of Biophysics cording to standard procedures to detect forms in the synthetic (S) and mitotic phases (M) of cell cycle [11] with Hoechst 33342 reagent (bisbenzimidazole fluorochrome; Sigma-Aldrich, St. Louis, Missouri, USA). CD133+, CD31+ cells, CD133+ AFP+, and CD31+ AFP+ double positive cells were stained using standard Miltenyi Biotec protocol for CD133/2 antibodies (Ab) conjugated with allophycocyanin (APC), BD Bioscience Pharmingen protocol for CD31 Ab with conjugated with fluorescein isothiocyanate (FITC), and R&D Systems protocol for α-fetoprotein (AFP) Ab conjugated with phycoerythrin (PE).…”
Section: Blood Samples For Flow Cytometrymentioning
confidence: 99%
“…CSCs evade chemotherapeutic attacks by expressing highly efficient efflux pumps [ 3 ]. The rapid extrusion of Hoechst 33342 is an established FACS-based technique with which this CSC (which can be defined and represented in FACS as a so-called “side population”, SP) can be quantified and enriched by “sorting” [ 4 , 5 ]. The CSC phenotype is characterized by, among other things, the expression of various surface markers.…”
Section: Introductionmentioning
confidence: 99%